Role of C5a-C5aR axis in the development of atherosclerosis - An, GuiPeng; Ren, GuoRui; An, FengShuang; Zhang, Cheng (Science China. Life sciences, 2014)
Complement component 5a（C5a）is a 74 amino acid glycoprotein and an important proinflammatory mediator that is cleaved enzymatically from its precursor,C5,on activation of the complement cascade.C5a is quickly metabolised by carboxypeptidases,forming the less-potent C5a desArg.C5a and C5a desArg interact with their receptors（C5aR and C5L2）,which results in a number of effects which are essential to the immune response.C5a has a broad range of biological effects throughout the human body because the widespread expression of C5a receptors throughout the human organs enables C5a and C5a desArg to elicit a broad range of biological effects.Recently,accumulating evidence in humans and experimental animal models shows that the C5a-C5aR axis is involved in the development of atherosclerosis lesions.The absence or blockade of C5aRs greatly reduces the formation of atherosclerotic lesions or wire-injury-induced neointima formation in atherosclerosis-prone mice.Serum C5a level was related to the major adverse cardiovascular events in patients with advanced atherosclerosis and those with drug-eluting stent implantation.Thus,the C5a-C5aR axis may be a significant pathogenic driver of arteriosclerotic vascular disease,making C5a-C5aR inhibition an attractive therapeutic strategy.